2008
DOI: 10.1111/j.1601-5223.1992.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative fragile sites in the horse karyotype

Abstract: After fluorouracil/5-bromodeoxyuridine synchronization and subsequent FPG-staining, the karyotype of 15 phenotypically normal horses displayed several breaks and gaps. Twelve bands 1q24, 4p12, 8q23, 11p12, 16q21, 17q21, 23q31, 23q32, Xp21, Xq22, Xq25 and Xq27 showed relatively frequent fragility. After thymidine/cytidine synchronization and subsequent GWL-banding the same horses display karyotypes without any fragility. Hence it is suggested that the above listed bands harbour folate and/or 5-bromodeoxyuridine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…(Paulsen and Ronne, 1991) and horse (Ronne, 1992). In river buffalo, Balakrishnan et al (1988) reported gaps on the X chromosome of anestrus females suggestive of a FS whereas Pires et al (1998) found FSs on the X chromosome in three breeds of river buffalo, but so far no detailed information is available on the localization of FSs on the karyotype of this species, whose banded karyotypes have been quite extensively characterized (Di Berardino et al, 1981;Di Berardino and Iannuzzi, 1984;Iannuzzi et al, 1990a) and standardized (CSKBB, 1994).…”
mentioning
confidence: 99%
“…(Paulsen and Ronne, 1991) and horse (Ronne, 1992). In river buffalo, Balakrishnan et al (1988) reported gaps on the X chromosome of anestrus females suggestive of a FS whereas Pires et al (1998) found FSs on the X chromosome in three breeds of river buffalo, but so far no detailed information is available on the localization of FSs on the karyotype of this species, whose banded karyotypes have been quite extensively characterized (Di Berardino et al, 1981;Di Berardino and Iannuzzi, 1984;Iannuzzi et al, 1990a) and standardized (CSKBB, 1994).…”
mentioning
confidence: 99%
“…The BrdU-sensitive fragile site, FRA13B, and aphidicolin-induced FRA13C, both localize to HSA13q21 [Hecht et al, 1990]. Fragility at this site was also observed in horses [Rønne, 1992] and in the cattle karyotype at the border between BTA12q22 and 12q23 [DiBerardino et al, 1983].…”
Section: Bovidaementioning
confidence: 82%
“…The table was constructed on the basis of comparative banding, cytogenetic map databases publicly available for each species, and previously published data. For example, conservation of a fragile site at HSAXq27 with horse, rabbit, and dog was suggested by Rønne [1992] along with shared fragility at Xq22 and HSA17q21/ECA13q21. Additional orthologous fragile sites have been described among primates, and between human and mouse [reviewed in Durkin and Glover, 2007;Helmrich et al, 2007].…”
Section: Domestic Animal Fragile Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakpoint region just distal to the centromere on ECA16 is near the HSA3q:3p inversion boundary and may represent yet another fusion or fission site contributing to the evolution of ECA16. Rønne (1992) identified 12 putative fragile sites in the horse. While fragile sites were identified on ECA1, ECA4, and ECA16, none of these sites correspond with the breakpoints described in this report.…”
Section: Discussionmentioning
confidence: 99%